Divergent trends of ecosystem status and services in the Hexi Corridor - Zhu, Hanshou; Zhai, Jun; Hou, Peng; Gao, Haifeng; He, Yingli; Jin, Diandian; Xu, Ningning (Frontiers in Environmental Science, 2022)
Based on the characteristics of ecosystem structure, quality and service, the ecosystem assessment framework of "State-Change-Interaction" is used to quantitatively analyze the ecological status and change characteristics of Hexi corridor. Comparing the changes and temporal and spatial differences of county scale ecosystem in 2000-2010 and 2010-2020, the results show that the ecosystem status, changes and interactions in Hexi corridor have similar spatial distribution patterns. From 2000 to 2020, the overall ecological status of Hexi Corridor improved. At the same time, compared with the previous decade, the hotspots of improving ecosystem quality and services in the Hexi Corridor has gradually moved eastward in the latter decade. Ecosystem change can significantly change the amount and relationship of ecosystem services, but the impact ways and spatial differences are obvious, and the impact reasons are diverse and complex. In general, multi-scale ecosystem comprehensive assessment, especially the scale coupling analysis of geographical units and administrative units, is conducive to the integration of strategic decisions and the implementation of specific policies and measures for ecosystem protection. It is also the scientific basis and prerequisite for formulating regional ecosystem protection and management strategies according to local conditions.